The Consultation with Experts Procedure in WTO Dispute Settlement System - Xin Xu; Lei Zhang (Journal of World Trade Studies, 2011)
Followed the rules of WTO covered agreements became more and more technical, and more and more disputes involved the expertise in the field of science or technology, the consultation with experts procedure became increasingly important. However, although the Panel is authorized by the WTO rules to start such a procedure, there are no detailed rules guiding the Panel as how to operate in the practice. Under such a circumstance, the Panel had to establish the temporary rules for this procedure after consultation with the parties to the dispute in each case. Many problems relevant to the due process then arose from such temporary rules. This paper tries to analysis the major problems thereof that receiving the most controversy and accusation, and will give suggestions as for how to reform and perfect this procedure.